2020
DOI: 10.1186/s13567-020-00861-2
|View full text |Cite
|
Sign up to set email alerts
|

Infection of bovine well-differentiated airway epithelial cells by Pasteurella multocida: actions and counteractions in the bacteria–host interactions

Abstract: Pasteurella (P.) multocida is a zoonotic pathogen, which is able to cause respiratory disorder in different hosts. In cattle, P. multocida is an important microorganism involved in the bovine respiratory disease complex (BRDC) with a huge economic impact. We applied air–liquid interface (ALI) cultures of well-differentiated bovine airway epithelial cells to analyze the interaction of P. multocida with its host target cells. The bacterial pathogen grew readily on the ALI cultures. Infection resulted in a substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 44 publications
0
12
1
Order By: Relevance
“…In addition, at this inoculation density, cilia coverage of the ALI at 24 hpi was significantly lower than in the control cultures with no bacteria . The authors concluded that this observation could be due to the lack of mucus-clearing in the ALI model compared to in vivo conditions …”
Section: In Vitro Respiratory System Modelsmentioning
confidence: 83%
“…In addition, at this inoculation density, cilia coverage of the ALI at 24 hpi was significantly lower than in the control cultures with no bacteria . The authors concluded that this observation could be due to the lack of mucus-clearing in the ALI model compared to in vivo conditions …”
Section: In Vitro Respiratory System Modelsmentioning
confidence: 83%
“…In addition, they are also considered one of the secondary exacerbation factors of BRD. Moreover, it is known that Pm and Mh were further infected in nasal mucosa when damaged by stress and/or viruses, and therefore, symptoms of the infected animals became more severe [ 39 , 40 ]. Our analysis exhibited that there were no significant differences in the detection of Mh- and Pm-specific genes between BRD-infected and healthy calves.…”
Section: Discussionmentioning
confidence: 99%
“…It causes pneumonia, genital infections, abscesses and septicemia. Thus, leads to shortage in production and high mortality rate (Su et al 2020). The current study was designed to evaluate the expression and immunogenicity of recombinant outer membrane protein A (OmpA) of P. multocida.…”
Section: Discussionmentioning
confidence: 99%